Anxiety, stress and depression in family members of patients with heart failure - Marianna Sobral Lacerda; Melissa Alves Cirelli; Alba Lúcia Bottura Leite de Barros; Juliana de Lima Lopes
Abstract OBJECTIVE Identifying the level of anxiety, stress and depression symptoms in family members of patients with heart failure; identifying the relationship between these feelings with sociodemographic and clinical variables. METHOD A cross-sectional study carried out with 100 family members. Depression, anxiety, and stress were evaluated by the Beck Depression and Anxiety Inventories and the Perceived Stress Scale - 10. The relationship between feelings and variables was performed through the t-test, Mann-Whitney or Kruskal-Wallis. RESULTS Mean depression was 8.24, anxiety was 77.95, and stress was 17.43. The correlation coefficient between depression and anxiety and depression and stress was 0.53, and it was 0.66 between anxiety and stress. Females (p=0.002, p=0.031), smoking (p=0.05, p=0.011) and sedentary lifestyle (p=0.023, p=0.001) were related to anxiety and stress, respectively. Family income lower than five minimum wages (p=0.012) was related to depression, and regular/poor self-perceived health status related to the three feelings. CONCLUSION Family members did not present high levels of these feelings. The scales were directly correlated with each one another and some variables were related to stress, anxiety and depression.